Las anfibolitas de la region de buitrago del lozoya (sistema central español) - Fernández Casals, M.J.; Casquet, C. (Cuadernos de Geología Ibérica, 1981)
Ca-Mg rocks cropping out in the region around Buitrago del Lozoya are classified, described, and their provenance explained in terms of estructures and geochemistry. Four types are distinguished here: Type 1 are para-amphibolites interbedded with schists and quarzites of likely Tremadoc age. Type 2 are also para-amphibolites inside the Buitrago Gneisses. These rocks contain relic minerals pointing to a high presure M, event (grossular almandine garnet, zoisite, rutile). Amphibolitization took place during an M2 intermediate low-pressure event of hercynian age. Type 3 are orto-amphibolites in the Buitrago Gneisses of a likely volcanic provenance and showing an associated polymetallic ore. Type 4 are para-amphibolites inside the El Cardoso volcano-sedimentary augengneisses. A correlation with amphibolites from other areas of the Spanish Hercynian Belt is considered.